SROI Analysis of the “Sayurpreneurship 4.0” Creating Shared Value Program by Master of Management, Airlangga University 2024 - Taufiq Muhammad Khozin; Gancar Candra Premananto (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
The advancement of technology in the digital era 4.0 has driven a significant shift in business models, from conventional to digital, requiring entrepreneurs to adapt in order to enhance efficiency and competitiveness. The Creating Shared Value (CSV) program titled Sayurpreneurship 4.0: Digitalization Strategy for Vegetable Vendors, initiated by Master of Management students from the Faculty of Economics and Business, Universitas Airlangga in 2024, represents a community engagement effort aimed at empowering traditional vegetable vendors through digital transformation. This quantitative study collected primary data through observation and interviews with program stakeholders to evaluate the social impact of the initiative. The results of the Social Return on Investment (SROI) calculation indicate that every Rp1 invested generates a social return of Rp7.04. These findings highlight that the digitalization of traditional vegetable vendors not only creates significant social value but also contributes to the achievement of Sustainable Development Goals (SDGs) Nos. 1, 4, 8, and 10. The study emphasizes the urgency of accelerating digital transformation among micro and small enterprises, fostering a modern business mindset, and developing similar high-impact social investment programs in the future.